Isolation of Serratia Marcescens (Isolate 30) and Partial Purification of Its Acrylamide-Degrading Amidase - Azmi, Nina Suhaity (2005)
A total of 217 bacterial isolates were isolated by an enrichment procedure from Malaysian soils which had been treated and non-treated with acrylamide. From the preliminary screening using MTT (3-[4,5-dimethylthiazol-2-yl]-,5- diphenyltetrazoliumbromide) assay, 10 bacterial isolates were found to be capable of utilizing acrylamide as a nitrogen source. Formation of the blue colour of formazan and high absorbance were the criteria in the selection of bacteria. These ten isolates were labeled as Isolate 5, 9, 10, 15, 30, 45, 60, 110, 115 and 145. The isolates were subjected to secondary screening using MTT assay, Direct Plate Count and High Perfomance Liquid Chromatography (HPLC). From the results obtained, five bacterial isolates, Isolate 9, 10, 15,30 and 60 gave the highest colony count in CFUI mL and absorbance reading from the MlT assay. These five bacterial isolates were then selected for further of examined for their ability to degrade acrylamide by HPLC. Isolate 30 showed the best degradation of acrylamide with 99.84% degradation after 48 hours incubation in enrichment culture with acrylamide as a substrate at a final concentration of 100 m a . Isolate 60 showed the second highest degradation of acrylamide at 70.53%, followed by Isolate 10 at 50.8% degradation and isolates 15 and 9 at 16.24% and 14.58% respectively. Control without bacteria accounted only 0.16% acrylamide degradation. Isolate 30 was selected for optimization of growth media with six different parameters. These parameters were temperature, pH, different types of carbon sources, different concentrations of carbon source, different amides as the substrate and effect of different concentrations of selected amide substrate. From the results obtained, Isolate 30 showed an optimum growth temperature at 27 " C. Its highest colony count loglo cfulml was directly proportional to the growth of bacteria. This isolate showed the highest growth at pH 7.5 where this type of bacteria grew well near neutrality and slightly alkaline media. For the carbon sources optimization, glucose was selected due to the high colony count. Isolate 30 was found to grow best at the glucose concentration of 1%. Among the amide substrates, acrylamide was found to be the best sole nitrogen source which can support bacterial growth in enrichment cultures and the bacteria showed the highest colony count when 400 mg/L acrylamide was provided. From the macroscopic and microscopic observations of Isolate 30, the bacteria was gram-negative rod, might become differentiated into a convex, pigmented and relatively opaque centre and an effuse, colourless, almost transparent periphery with an irregular crenated edge. Biochemical tests using Microbact 24E (12A + 12B) showed that the Isolate 30, which had been isolated from Tanjung Karang, Selangor gave 99.83% similarity to Serratia marcescens. Amidase (EC 3.5.1.4) produced by Serratia marcescens strain 30 was partially purified and characterized. The purification procedure used, including ionexchange chromatography, M O ~ O - Qs~tro ng-anion exchanger, ultrafiltration and gel filtration, yielded a partially purified amidase fraction having an overall purification factor of 13.83 fold and a yield of 48.33%. Indophenol blue method was used for the amidase assay and arnidase characterization studies was done to determine the K, and Vmax value, the effect of temperature and pH on amidase activity and the effect of heavy metals on amidase activity. K, values for acrylamide were determined by incubating amidase at 50" C with various concentrations of acrylamide (0.25 to 2 0 M ) in phosphate buffer (50mh4; pH 7.5). By using non-linear regression analysis, the Km and Vmax values were 0.9376mM acrylamide and 60.92 pmol ammonia disappearecUmin respectively. The amidase exhibited maximal activity at 50" C and pH value at 7.5. The result of effects of heavy metals on amidase activity showed that AgN03 and CuC12 inhibited amidase activity while HB03 enhanced amidase activity. The enzyme is a monomer with an apparent molecular weight of 1 1 1 kDa.